Surgical Management of Spinal Dysraphism: Five -year Experience in a Central Hospital - Banskota, N; Jha, R; Khadka, N; Sharma, GR; Bista, P; Kumar, P (Journal of Nepal Paediatric Society, 2014)
Introduction: Spinal dysraphism is a heterogeneous group of congenital spinal anomalies resulting from defective closure of the neural tube early in fetal life and anomalous development of the caudal cell mass. Meningomyelocele is common among Neural tube defects. Patients with myelomeningocele present with a spectrum of impairments, including primary functional deficits like are lower limb paralysis, sensory loss, bladderbowel dysfunction and cognitive dysfunction. Medical, surgical management and rehabilitation have helped patients with neural tube defects to participate and be productive in mainstream society. The aims of this study were to review the clinical presentation, surgical management and their outcome in the patient with spinal dysraphism. Materials and Methods: This is a retrospective study of Forty-one cases of spinal dysraphism managed during a period of five years from January 2008 to December 2012 in Department of Neurosurgery, National Academy of Medical Sciences (NAMS), Bir Hospital. Demographic profiles, clinical presentation of patients with spinal dysraphism, associated hydocephalus, surgical management and outcome were studied. Results: Out of total 41 cases studied, male patients outnumbered female with 58.5% to 41.5%. Age ranged from 5 days to 29 years and mean age was 2.71 years whereas. Lump (97%) and paraparesis (88%) were frequent mode of presentation. Lumbar lesion (65%) was commonest followed by lumbosacral (29%). Hydrocephalus was present in 51% of cases and in 24% cases developed hydrocephalus later after repair. Total 75.6% of cases were treated with VP shunt. Conclusion: Spinal dysraphism is debilitating entity and management is challenging. Lump on back and weakness of limb are major factor for children and their parents seek medical service. Lesion in low back (lumbar and lumbosacral) were most common location. Besides repair, majority of them needed CSF diversion surgery for hydocephalus. Aim of surgical management was to prevent further deterioration, control of hydrocephalus or leak. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9378 J Nepal Paediatr Soc 2014;34(1):34-38